HepParser: An Intelligent Software Program for Deciphering Low-Molecular-Weight Heparin Based on Mass Spectrometry - Wang, Hui; Wang, Yu; Hou, Meijie; Zhang, Chunming; Wang, Yaojun; Guo, Zhendong; Bu, Dongbo; Li, Yan; Huang, Chuncui; Sun, Shiwei (Frontiers in Chemistry, 2021)
Low molecular weight heparins (LMWHs) are considered to be the most successful carbohydrate-based drugs because of their wide uses as anticoagulants in clinic. The efficacy of anticoagulants made by LMWHs mainly depends on the components and structures of LMWHs. Therefore, deciphering the components and identifying the structures of LMWHs are critical to developing high-efficiency anticoagulants. However, most LMWHs are mixtures of linear polysaccharides which are comprised of several disaccharide repeating units with high similarity, making it extremely challenging to separate and decipher each component in LMWHs. Here, we present a new algorithm named hepParser to decipher the main components of LMWHs automatically and precisely based on the liquid chromatography/mass spectrometry (LC/MS) data. When tested on the general LMWH using hepParser, profilings of the oligosaccharides with different degrees of polymerization (dp) were completed with high accuracy within one minute. When compared with GlycReSoft in heparan sulfate samples, hepParser achieved more comprehensive and reasonable results automatically.